Copper Oxide Nanoparticles Stimulate Cytotoxicity and Apoptosis in Glial Cancer Cell Line - Kukia, Nasim Rahmani; Abbasi, Ardeshir; Froushani, Seyyed Maysam Abtahi (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Due to cytotoxic potential, Copper Oxide Nanoparticles (CuO NPs) have recently been studied in various in vivo and in culture cell line. Also, CuO has received much attention in cancer therapy. We aimed to evaluate the cytotoxicity of CuO NPs on glial cancer (B92) cell line. B92 cancer cells were cultured with CuO NPs at different concentrations (5, 10, and 20 μg/ml) with 30 and 60 nm particle size. Then, cancer cells were incubated for 24 hrs. The apoptosis and cytotoxicity of cells were estimated by acridine orange/propidium iodide staining and MTT assay, respectively. Both sizes of CuO NPs had cytotoxic effect. Even with the lowest concentration, the cytotoxic impact accommodated 32% of cell apoptosis with 30 nm size. When the concentration of CuO NPs increased, viability decreased and apoptosis increased. However, these amounts have no significant changes in the concentration of 10 to 20 μg/ml between two particle sizes (30 and 60 nm). The IC50 was decreased as the size of particles increased, but there was no significant change. This finding suggests that exposure to CuO NPs had significant cytotoxic effect with the sizes tested when compared to unexposed control in a way that the smaller size and higher concentration exerted the maximum cytotoxic effects. It seems that augmentation may not have any impact on their in vitro cytotoxicity. Dhaka Univ. J. Pharm. Sci. 17(1): 105-111, 2018 (June)